Lipase production by Aspergillus niger using sheanut cake: an optimization study - Salihu, Aliyu; Bala, Muntari; Alam, Md Zahangir (Elsevier B.V, 2016)
The effects of medium components affecting lipase production by Aspergillus niger AS-02 using sheanut cake (SNC) were studied based on the one-factor-at-a-time (OFAT) method and the face-centred central composite design (FCCCD). Of the six medium components analysed by OFAT, three (Tween-80, (NH4)2SO4 and Na2HPO4) were subjected to FCCCD. Under optimized conditions, the obtained lipase production showed good agreement between the experimental (49.37 U/g) and predicted (48.81 U/g) yields, with a coefficient of determination (R2) of 0.96. The optimum medium components were 1.0% (v/w) Tween-80, 0.35% (w/w)(NH4)2SO4 and 0.40% (w/w) Na2HPO4. The findings in this study showed that, in addition to lipase production, the fermented SNC had reduced tannin and saponin contents, which are the major components that limit the use of SNC in feed formulations.